PENGARUH PRICE FAIRNESS, SERVICE A QUALITY, DAN PRODUCT QUALITY TERHADAP CUSTOMER LOYALTY PADA ONLINE SHOP MILANINT KEDIRI - Lubena Wulandari; Ustadus Sholihin; Iing Sri Hadiningrum (Cahaya Ilmu Bangsa, 2024)
This research aims to determine the influence of price fairness, service quality, and product quality on customer loyalty. The research method used is a quantitative method with a descriptive approach. Data collection in this research was carried out by distributing questionnaires to Milanint customers and calculated using the SPSS Version 25 application. The population in this study was all customers at Milanint, totaling 260 slovin formulas. Data analysis techniques used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test, and R2 Coefficient of Determination Test. In the validity test, it is known that all statement items on the variables (X1, X2, X3 and Y) have a significance value of 0.000 < 0.05, so that each variable is declared valid. Then in the reliability test it was discovered that each variable had a Cronbach's Alpha value > 0.60 so that the variable was declared reliable. Furthermore, in the t test it was discovered that all variables (price fairness, service quality, and product quality) had a positive value and a significance of <0.05 so that it was stated that they partially had a significant effect on purchasing decisions. Then in the F test the Sig value is known. for all variables together it is 0.000 < 0.05 and the value of Fcount > Ftable, it can be concluded that the variables price fairness, service quality and product quality simultaneously influence customer loyalty at the Milanint Kediri Onlineshop